Description of The Planning Stages of Drug Needs and Drug Distribution in Ndetundora Public Health Center, Ende Regency - Margareta Elisabeth Kartona Aru; Muntasir Muntasir; Masrida Sinaga (Universitas Nusa Cendana, 2022)
Poor planning and distribution generally cause drug expiration problems. Therefore, planning and distribution activities must be carried out according to accounting rules. The purpose of this study was to describe the stages of planning for drug needs and drug distribution at the Ndetundora Community Health Center (Puskesmas). The type of research used was qualitative research. There were three informants in this study whose positions and duties were related to the planning and distribution of drugs. The results showed that at the planning stage of drug needs, the selection was based on the disease most suffered by patients who visited the Puskesmas and referred to DOEN and FORNAS. Drug needs data were collected from all network services at the Puskesmas and calculated using the morbidity/epidemiology method. The research also found problems related to excesses and expired drugs. The problems resulted from the discrepancy between the types of drugs received and the drug requests submitted by the Puskesmas. The Ndetundora Public Health Center and the parties involved need to evaluate and find solutions to the problems in planning and distributing drugs that result in expired and excess drugs.